Analisis Parameter Fisik Tanah Pada Daerah Rawan Longsor Di Kelurahan Battang Barat Kota Palopo Sebagai Mitigasi Dini Bencana Longsor - Pariabti Palloan; Nur Aminuddin Ansar; Sulistiawaty; Agus Susanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study investigates physical properties parameters of the soil in landslide prone areas in West Battang Village, Palopo City. This study aimed was to determine the grain size of the soil, the value of soil permeability, and the distribution characteristics of the soil in landslide-prone areas. The 30 samples were taken randomly at a depth of 30 cm, then tested the soil grain size, permeability, and the samples distribution. The results showed that the grain size of the soil consisted of gravel, coarse sand, medium sand, and fine sand, with a size of approximately 0.075 – 4.75 mm. The soils in West Battang Village are dominated by sandy soil. The grains soil in the West Battang Village is dominated by coarse sand. The physical characteristics of the soil grains in this area are classified as poorly graded due to incomplete grain size with soil permeability values in the range of 0.5 – 2.0 cm/hour which can absorb water in category of moderately slow. These permeability values can be categorized as a moderately slow and can stimulate landslides due to gradually accumulation of water in the soils.